Investigating women and men convicted of white-collar offenses on federal community supervision: sample and methods - Harbinson, Erin (Criminal justice studies, 2020)
This paper reviews the sample and methods used for the three papers in this special issue that focus on gender differences and similarities among people convicted of white-collar offenses under community supervision. Context is provided regarding the origins of the papers for this special issue and their subsequent approach to the study of gender and white-collar crime. Detail is provided on the data set used for this study, which was originally developed from the Administrative Office of the United States Courts in order to study federal probation’s risk and needs assessment tool. Finally, the paper describes how people sentenced for white-collar types of crimes were selected for inclusion in the papers for this special issue.